2016
DOI: 10.4085/1062-6050-49.5.22
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Lower Extremity Injury in a Military Cadet Population After a Supervised Injury-Prevention Program

Abstract: Context: Specific movement patterns have been identified as possible risk factors for noncontact lower extremity injuries. The Dynamic Integrated Movement Enhancement (DIME) was developed to modify these movement patterns to decrease injury risk.Objective: To determine if the DIME is effective for preventing lower extremity injuries in US Military Academy (USMA) cadets.Design: Cluster-randomized controlled trial. Setting: Cadet Basic Training at USMA. Patients or Other Participants: Participants were 1313 cade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Most studies involved only male participants, but four studies also included female participants (ranging from 10% to 40% female). [38][39][40][41] Two studies did not report on gender. 42,43 Study details are presented in detail in online Appendix C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies involved only male participants, but four studies also included female participants (ranging from 10% to 40% female). [38][39][40][41] Two studies did not report on gender. 42,43 Study details are presented in detail in online Appendix C.…”
Section: Resultsmentioning
confidence: 99%
“…One trial 38 explored the effects of a dynamic integrated movement enhancement warm-up, compared to an active warm-up, before engaging in sports or other intense physical training on the incidence of lower extremity injuries. This study found no difference between the groups (RR = 1.02, 95% CI 0.85-1.22).…”
Section: Movement Enhancement Warm-upmentioning
confidence: 99%
“…There was a signi cant association between the attitudes subscale, comprised of questions related to barriers and bene ts of participation, and intention to participate (15). There are multiple bene ts to participating in ERIPPs within military personnel including reduction in the risk of lower extremity injury (24) and improvements in functional performance (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that injury-prevention programs targeting high-risk biomechanical movement patterns may be effective in the primary prevention of acute traumatic knee-joint injury, 50,51 and these programs may be applicable to military training populations. 52 Information on effective acute traumatic injury-prevention strategies for other joints is currently limited in the literature.…”
Section: Discussionmentioning
confidence: 99%